Tennessee Fruit and Vegetable Farmers’ Willingness to Adopt Alley Cropping Systems - Margarita Velandia; Carlos Trejo-Pech; David Butler; Le Chen; Annette Wszelaki; Karen L. DeLong; Susan Schexnayder; Hasibul Hasan Shanto (HortTechnology, 2025)
Alley cropping is an agroforestry practice that involves the planting of trees or shrubs alongside herbaceous crops within the same production system. Potential benefits of alley cropping include crop diversification, enhanced productivity of annual crops, reduced soil erosion, improved pollinators and wildlife habitat, decreased incidence of pests and diseases, carbon sequestration, and reduced nitrogen leaching. Despite these potential benefits, the adoption of alley cropping remains low. In Tennessee, specifically, only about 2% of the farms have used agroforestry practices, including alley cropping. We surveyed Tennessee fruit and vegetable farmers to assess their willingness to adopt alley cropping and the differences in characteristics of those willing and not willing to use this production practice. In general, those respondents who are willing to adopt alley cropping are more familiar with this production system and are facing or have faced production challenges that could be alleviated by adopting this production practice, such as low organic matter and crop heat stress. Our results also suggest that the type of trees or shrubs incorporated in this system and adequate payment for adoption that covers investment and maintenance costs could affect Tennessee fruit and vegetable farmers’ willingness to use this system.